Relación entre la conciencia quirúrgica y la seguridad del paciente, basada en la teoría de benner - López Campaña, Leny Alejandra (2025)
The study focused on the surgical awareness and its impact on patient safety highlighting the importance of expert nurses accompanying novice nurses. The objective was researching how surgical awareness can improve the patient safety in the surgical environment through the support and mentorship of experienced professionals. A qualitative approach was used by carrying out a bibliographic review of previous studies that allowed to analyze the experiences and perceptions of nurses in surgical contexts. The results showed that the continuous training and support from experienced nurses are crucial for novice nurses to develop necessary competences in the clinical practice. Additionally, barriers in communication and knowledge on surgical awareness were identified which emphasizes the necessity of a strategy to strengthen decision-making and patient care. This study provided a theoretical framework that can lead future research emphasizing that the support of expert nurses is essential to improve the surgical awareness and therefore, the patient safety.